Interpersonal Trust dengan Self Disclosure Pengguna Akun Pseudonim Media Sosial Pada Generasi Z - Adilla, Tarisha Asya; Merida, Sarita Candra (Madani: Jurnal Ilmiah Multidisiplin, 2025)
Abstract This study aims to determine the influence of interpersonal trust on the self-disclosure of pseudonymous social media account users in generation Z. The research method used is descriptive quantitative with purposive sampling technique. The population in this study is not known for sure, the number of samples to be searched using the Cochran formula with a margin of error of 5%. So that the number of samples in this study is 403 Generation Z who are active in using pseudonymous social media accounts X. Data collection uses two scales, namely the interpersonal trust scale from Rotenberg's theory (2010) and the self-disclosure scale from Wheeless 's theory (1978). The results showed that the majority of respondents had a moderate level of interpersonal trust and self-disclosure. Therefore, it can be concluded that interpersonal trust contributes to the level of self-disclosure, and the use of pseudonymous accounts is not necessarily an obstacle to building open and meaningful relationships in the digital world.